PENGARUH GAYA KEPEMIMPINAN DEMOKRATIS DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN PADA PT. STARINDO MITRADASA CIPTA JAKARTA SELATAN - sari, yeni nopita; Sudarso, Aden Prawiro (Publika Citra Media, 2025)
This study aims to analyze the influence of democratic leadership style on employee performance, to determine the influence of communication on employee performance, and to determine the influence of democratic leadership style and communication on employee performance at PT. Starindo Mitradasa Cipta South Jakarta. The method used is a quantitative method using associative. The sampling technique used is saturated sampling using a sample of 63 respondents. Data analysis uses regression analysis,correlation coefficient analysis, determination coefficient analysis and hypothesis testing. The results of this study are that the democratic leadership style variable has a level of relationship or influence of 0.619 on employee performance),from the hypothesis tester obtained a calculated t value> t table (5.494> 2.000). This is strengthened by a significant value of 0.000 <0.050. For this reason, the hypothesis H0 is rejected and H1 is accepted, meaning that there is a positive and significant influence between democratic leadership style on employee performance at PT. Starindo Mitradasa Cipta South Jakarta. Communication has a positive and significant effect and has a level of relationship or influence of 3.543 on employee performance. From the hypothesis testing, the calculated t value was obtained > t table (3.543 > 2.000). This is reinforced by a significant value of 0.001 <0.050, so H0 is rejected and H2 is accepted. The hypothesis test of democratic leadership style and communication has a positive and significant effect on employee performance with a determination coefficient of 68.5% while the remaining 31.5% is influenced by other factors. The simultaneous hypothesis test obtained a calculated F value> F table (65.295> 3.15). This is also reinforced by a probability significance value of 0.000 <0.050. Therefore, H0 is rejected and H3 is accepted, meaning that there is a positive and significant simultaneous influence between democratic leadership style and communication on employee performance at PT. Starindo Mitradasa Cipta South Jakarta.